Politics of Gender (in)Equality Relating to Sport and Development Within a Sub-Saharan Context of Poverty - Burnett, Cora (Frontiers in Sociology, 2018)
Gender represents a confounding social construction within the multiple-layering of relative disenfranchisement in the Sub-Saharan context of poverty. Class and race play a significant role in the socialisation process, structures and policy frameworks that contribute to the perpetuation of gender inequalities in broader society and within different sport-related spheres. This paper draws on the conceptual insights of Marxian and Feminist approaches, socialisation literature and the understanding of the social inequality of condition, opportunity and capacity. It aims to reflect critically on the lived-realities of women in post-Apartheid South Africa to illustrate how ideology, culture, significant others, the availability of resources and democracy continue to shape the lives of women and girls. A discussion of policy frameworks, from the global to the local levels and experiences of how people 'do gender', are discussed. Main study data entails that from a ten-year review (1994-2004) on the status of South African women in sport and recreation and from three case studies linked to a sport-for-development 2010 FIFA World Cup legacy project. The latter entails the impact assessment of the GIZ/YDF (German Development Corporation Youth Development through Football) programme over a period of seven years (2007-2014). Data were updated and re-interpreted in view of current gender discourses and public debates around gender inequality. Patriarchal ideology and hegemonic gender structures and practices continue to contribute to barriers women and girls face to participate in traditionally male sports and for gaining access to leadership positions. Enabling factors for addressing gender equality exist within the policy frameworks and human agency, where male gate-keepers filter access to gender inclusivity and empowerment. Gender inequality has taken the backseat to social transformation in post-Colonial contexts and should feature prominently on public agendas with mechanisms in place for monitoring and evaluating progress. It necessitates structural and systemic reform beyond current piece meal offerings and neo-Liberal initiatives to hold girls and women responsible for their own enlightenment and full participation in sport and society.